The Effect of Myofascial Release and Cervical Traction on Pain, Range of Motion and the Neck Disability Index in Patients with Chronic Neck Pain: A Randomized Controlled Trial (London Journal of Medical and Health Research, 2024)
Purpose: This study examined the effects of the myofascial release and cervical traction after applying conservative physical therapy to patients chronic neck pain. Methods: Patients were randomly divided into two groups, namely myofascial release (7 subjects) and cervical traction (7 subjects). Each group performed their therapy 45 minutes per day, two times a week, for four weeks. Pain intensity was measured using the visual analog scale (VAS). Function was measured with the neck disability index (NDI). The cervical range of motion (CROM) was measured with a cervical range of motion (CROM) goniometer. Results: After four weeks of therapy, the VAS (p < .05) and NDI (p < .05) significantly decreased, and ROM significantly increased in both groups (p < .05). There were also significant differences between the two groups for these three measures, except for neck flexion and neck extension(p
Keywords: Vanoxerine consta; Stimulant (Amphetamine-Type Substances/ATS) dependence; long-term delivery; PLGA polymers; enzymes.; collagenase; recombinant.; Skin flaccidity; sagging skin; hyaluronic acid; quality; Efficiency; Optimization; Turnaround time; appointment schedule; Affects; predictive coding; simulation; Markovblanket; RSI paradigm.; Cervical traction; Chronic neck pain; NDI; Myofascial release; VAS